Intelligent Street Light Monitoring System Using Wireless Sensor Network - Zul Zarif Bin Sharkawi, Zul Zarif (2010)
This aim of this project is to develop a system to monitor the condition of the street light using wireless network. To achieve this objective, a sensor is developed and to be placed at a street light. The project concerns about the communications between a few sensors, one on a street light with another one on a different street light.